2018
DOI: 10.3341/kjo.2017.0075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anterior, Posterior, and Total Corneal Astigmatism Measured Using a Single Scheimpflug Camera in Healthy and Keratoconus Eyes

Abstract: PurposeTo compare the effect of posterior corneal astigmatism on the estimation of total corneal astigmatism using anterior corneal measurements (simulated keratometry [K]) between eyes with keratoconus and healthy eyes.MethodsThirty-three eyes of 33 patients with keratoconus of grade I or II and 33 eyes of 33 age- and sex-matched healthy control subjects were enrolled. Anterior, posterior, and total corneal cylinder powers and flat meridians measured by a single Scheimpflug camera were analyzed. The differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some have reported that astigmatism at the corneal posterior surface was generally less than 0.50DC. [ 18 19 20 21 22 23 24 25 26 ] It has been claimed that Orbscan II tends to overestimate characteristics of the posterior corneal surface compared with other systems. [ 5 27 ] Alternatively, it could equally be argued that other systems underestimated changes at the posterior surface of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that astigmatism at the corneal posterior surface was generally less than 0.50DC. [ 18 19 20 21 22 23 24 25 26 ] It has been claimed that Orbscan II tends to overestimate characteristics of the posterior corneal surface compared with other systems. [ 5 27 ] Alternatively, it could equally be argued that other systems underestimated changes at the posterior surface of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [108,109] demonstrate the utility of this technique in the diagnosis and monitoring of keratoconus. In addition, through the modality of corneal tomography that this technique offers, monitoring the risk of ectasia [110,111].…”
Section: B Scheimpflug Imaging Systemsmentioning
confidence: 99%